The Development of Comic Mathematics Media with PMRI Approach on Social Arithmetics for Seventh Grade Junior High School - Tri Murdiyanto; Lukman El Hakim; Ayuniar Thamril (Jurnal Pendidikan Matematika IKIP Veteran Semarang, 2022)
This research aims to develop media of comic mathematics with realistic mathematics education Indonesia approach on social arithmetics for seventh-grade junior high school. This developmental research develops a comic of mathematics using the development model from Borg and Gall with five stages. The five stages are (1) Need analysis for teacher dan students; (2) planning and developing the product; (3) the validation from material and language experts and media experts; (4) small group test; (5) significant group test. The data were analyzed using qualitative and quantitative analysis techniques. The feasibility of the product was assessed by processing data from a questionnaire based on the validation results of media experts, validation of material and language experts, teachers, and students not only in a small group test but also in a significant group test. The result of this research is a comic of mathematics with a realistic mathematics education approach to social arithmetics. Based on this research, the percentage of the product feasibility was 86,40%, categorized as very feasible. Based on data, it can be implied that the media of comic mathematics with a realistic mathematics education approach to social arithmetics is feasible to use. Keywords: Learning Media, Comic Mathematics, Social Arithmetics